2019
DOI: 10.3912/ojin.vol24no03ppt22
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers Impeding Nurse Activation of Rapid Response Teams

Abstract: Management of rapid patient deterioration requires prompt recognition and swift response by bedside nurses and specially trained personnel, who successfully intervene to improve patient outcomes. Timely recognition and activation of rapid response mechanisms requires prudent nursing care. When patient needs and nurse competencies are unbalanced, patient outcomes decline and nurse confidence diminishes. This article offers a brief background of rapid response, including the supporting theoretical framework. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Failure to recognize early signs and symptoms and initiate timely clinical interventions results in poor patient outcomes and this failure has been attributed to registered nurses" (RN) lack of knowledge and confidence (Lee et al, 2019). However, it has also been suggested that Registered Nurses (RN) do have relevant knowledge, but fail to respond appropriately to patient deterioration because they are not able to recognize and act upon abnormal vital signs (Butler, 2018;Clayton, 2019;Duff et al, 2020;Sterner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Failure to recognize early signs and symptoms and initiate timely clinical interventions results in poor patient outcomes and this failure has been attributed to registered nurses" (RN) lack of knowledge and confidence (Lee et al, 2019). However, it has also been suggested that Registered Nurses (RN) do have relevant knowledge, but fail to respond appropriately to patient deterioration because they are not able to recognize and act upon abnormal vital signs (Butler, 2018;Clayton, 2019;Duff et al, 2020;Sterner et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A multidisciplinary team is involved in the decision making that takes place during the PPCI pathway, including the nurse activator who plays a vital role in the activation of the pathway. Interdisciplinary teamwork and collaboration have been previously discussed as key factors involved in the decision making ability of nurse activators (Clayton, 2019). Personalities of each team member may play a role in the decision making and relationships between these personalities could perhaps influence decisions.…”
Section: Type Of Error Being Avoidedmentioning
confidence: 99%